2021
DOI: 10.3389/fmicb.2021.630302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intercropping on the Diazotrophic Community in the Soils of Continuous Cucumber Cropping Systems

Abstract: Diazotrophs are important soil components that help replenish biologically available nitrogen (N) in the soil and contribute to minimizing the use of inorganic N fertilizers in agricultural ecosystems. However, there is little understanding of how diazotrophs respond to intercropping and soil physicochemical properties in cucumber continuous cropping systems. In this study, using the nifH gene as a marker, we have examined the impacts of seven intercropping plants on diazotrophic community diversity and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Continuous monoculture adopted in the cultivation of Cucumis sativus , an important horticultural crop, has caused problems such as yield reduction and quality deterioration [ 32 , 33 ]. Intercropping has proved to be a sustainable way to solve these problems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous monoculture adopted in the cultivation of Cucumis sativus , an important horticultural crop, has caused problems such as yield reduction and quality deterioration [ 32 , 33 ]. Intercropping has proved to be a sustainable way to solve these problems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the authors also noted that the abundance of the nifH gene was increased when soybean and corn were cropped in rotation compared to continuous cropping. Similarly, Gao et al (2021) showed that rape-cucumber intercropping increased the abundance of the nifH gene, diazotrophic diversity, and richness, which were higher than in the monoculture. However, cropping season had a more significant effect than intercropping.…”
Section: Non-symbiotic Nitrogen Fixationmentioning
confidence: 94%